دراسة نتائج تجريف الرحم الاستقصائي لدى مريضات النزف الرحمي الشاذ - عبد الرحمن أحمد; بدور غازي; عبده وجدي (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 117 مريضة راجعن المشفى بشكوى نزف رحمي شاذ وأخضعن لإجراء تجريف رحم استقصائي مجزأ. جاءت النتائج كالآتي: شكلت الموجودات السلبية لبطانة الرحم النتيجة الأعلى (39.32%)، وكان تواجد فرط تصنع بطانة الرحم البسيط كموجودة نسيجية مفردة مرتفعا" (37.61%)، وترافق فرط تصنع بطانة الرحم البسيط مع بوليبات بطانية أو التهاب بطانة الرحم في (2.56% و 0.85%) من الحالات بالترتيب ، و وجدت اللانموذجية النووية في 2.17% من جميع حالات فرط تصنع بطانة الرحم البسيط . وجد فرط تصنع بطانة الرحم المعقد في (6.84%) من الحالات، و وجدت اللانموذجية النووية في( 37.5%) من حالاته. وجد سرطان بطانة الرحم في (2.56%) من الحالات وكانت جميعها عند مريضات النزف الرحمي بعد سن اليأس. وجدت بوليبات بطانة الرحم والتهاب بطانة الرحم كموجودة نسيجية مفردة عند (8.55 % و 1.71%) من الحالات بالترتيب. This study includes 117 patients who came to hospital with a complaint of abnormal uterine bleeding and underwent fractional diagnostic curettage. The results were: Negative findings of the endometrium formed the highest result (39.32%). Simple endometrial hyperplasia as a single finding had a high prevalence of (37.61%). The combination of simple endometrial hyperplasia and endometrial polyps or endometritis was found in 2.56 and 0.85 percent respectively of all cases, atypia was found in 2.17% of all cases of simple endometrial hyperplasia. Complex endometrial hyperplasia was found in (6.84%) of cases, and atypia was found in (37.5%) of all its cases. Endometrial carcinoma was found in (2.56%) of all patients and all were found in postmenopausal patients. Endometrial polyps and endometritis as a single finding were found in 8.55 and 1.71 percent respectively of all cases.